Your undergraduate dissertation the essential guide for success - Walliman, Nicholas S. R. (Sage study skills, 2014)
This guide to all the essential facets of dissertation writing at undergraduate level provides advice for preparing a project and choosing a topic, and guidelines for writing a project proposal and producing a literature review.